Platelet-Targeted FVIII Gene Therapy Restores Hemostasis and Induces Immune Tolerance for Hemophilia A - Cai, Yuanhua; Shi, Qizhen (Frontiers in Immunology, 2020)
Platelets are small anucleated blood components primarily described as playing a fundamental role in hemostasis and thrombosis. Over the last decades, increasing evidence has demonstrated the role of platelets in modulating inflammatory reactions and immune responses. Platelets harbor several specialized organelles: granules, endosomes, lysosomes, and mitochondria that can synthesize proteins with pre-stored mRNAs when needed. While the functions of platelets in the immune response are well recognized, little is known about the potential role of platelets in immune tolerance. Recent studies demonstrate that platelet-specific FVIII gene therapy can restore hemostasis and induce immune tolerance in hemophilia A mice, even with pre-existing anti-FVIII immunity. Here, we review the potential mechanisms by which platelet-targeted FVIII gene therapy restores hemostasis in the presence of anti-FVIII inhibitory antibodies and induces immune tolerance in hemophilia A.